2022
DOI: 10.3389/fneur.2022.797791
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of the Early Prediction of Functional Outcome After Stroke Prediction Model for Independent Gait at 3 Months After Stroke

Abstract: IntroductionThe Early Prediction of Functional Outcome after Stroke (EPOS) model for independent gait is a tool to predict between days 2 and 9 poststroke whether patients will regain independent gait 6 months after stroke. External validation of the model is important to determine its clinical applicability and generalizability by testing its performance in an independent cohort. Therefore, this study aimed to perform a temporal and geographical external validation of the EPOS prediction model for independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(48 reference statements)
1
2
0
Order By: Relevance
“…In the development study, 5 they found that the TCT-3 and the MI leg score on the ninth day could predict independent walking at 6 mos poststroke with 92% accuracy. However, as expected, these values decreased in the validation cohort 36 : TCT-3 and the MI leg score on the ninth day poststroke, could predict independent walking at 3 mos after stroke with 86% accuracy (overall accuracy = 0.86, sensitivity = 0.93, specificity = 0.65).…”
Section: Validationsupporting
confidence: 72%
See 2 more Smart Citations
“…In the development study, 5 they found that the TCT-3 and the MI leg score on the ninth day could predict independent walking at 6 mos poststroke with 92% accuracy. However, as expected, these values decreased in the validation cohort 36 : TCT-3 and the MI leg score on the ninth day poststroke, could predict independent walking at 3 mos after stroke with 86% accuracy (overall accuracy = 0.86, sensitivity = 0.93, specificity = 0.65).…”
Section: Validationsupporting
confidence: 72%
“…Moreover, Veerbeek et al 36 recently published an article about the external validation of their EPOS study. An important difference with the development study of 2011 was that the outcome of interest was measured 3 mos after stroke (subacute phase) instead of 6 mos after stroke (chronic phase).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation